SISTIM PROPORSIONAL TERBUKA DALAM PERSPEKTIF DEMOKRASI PANCASILA - Jaidun, Jaidun (Jurnal Pengabdian Kreativitas Pendidikan Mahakam (JPKPM), 2023)
Indonesia is a large country that has an understanding of democracy, namely Pancasila democracy, in which in the life of the nation, the state is bound by Pancasila as the state philosophy, state ideology, the nation's view of life and the source of all sources of law. Indonesia in its democracy always prioritizes the principle of deliberation and consensus in order to achieve national goals. Representation in the general election system is a commitment of the nation since this country was founded by the founding fathers, including procedures for selecting people's representatives who will sit in the legislature (DPR) both using an open proportional system and a closed proportional system. . Basically the majority or even almost all Indonesian people as part of the people's responsibilities and obligations in electing national leaders want elected leaders who have religious morality, quality, accountability, transparency, honesty and integrity in the framework of realizing good and clean governance, because the people are the holders Sovereignty in a broad sense means that the people have the highest authority in determining the fate of the nation and state, therefore whatever the will of the people, the state is obliged to carry out as well as possible on behalf of the people's sovereignty.